Monitoring and evaluation of maritime spatial planning – A review of accumulated practices and guidance for future action. (April 2023) - van den Burg, S.W.K.; Skirtun, M.; van der Valk, O.; Cervi, W. Rossi; Selnes, T.; Neumann, T.; Steinmann, J.; Arora, G.; Roebeling, P.
Abstract: The Maritime Spatial Planning Directive 2014/89/EU requires implementation of spatial planning in the marine waters of EU Member States and the establishment of maritime spatial plans by Member States at the latest by 31 March 2021. In Directive 2014/89/EU it is explicitly mentioned that maritime spatial plans shall be reviewed by Member States as decided by them but at least every 10 years. This article aims to review accumulated practices in monitoring and evaluation of maritime spatial plans based on a review of literature, interviews and an expert workshop. Numerous approaches to monitoring and evaluation are applied and available. Monitoring and evaluation of maritime spatial plans is about more than the identification and use of best available methods, it requires sufficient skills and resources, for the evaluators and for stakeholders that might be involved. While not explicitly mentioned in the MSP Directive, equity in the allocation of marine areas for use is highlighted as an important emerging issue. Maritime developments are influenced by a mix of policies and linear approach to M&E fail to capture this complexity. The value of M&E is that is can improve the quality of MSP by instigating and structuring a participative processes with cross-sectoral and cross-border learning.